Study Quality of Voltage on Single Track AC Railway Traction Electrification - Andri Pradipta; Santi Triwijaya; Fathurrozi Winjaya; Arief Darmawan; Agustinus Prasetyo Edi W (Journal of Railway Transportation and Technology, 2023)
Voltage fluctuation is one of important parameter for power quality in electrification parameter. The voltage parameter is said to be good if the voltage level does not exceed or less than the standard voltage. In the operation of electric trains, several conditions can cause over and under voltage. Like when a train accelerates or decelerates it will affect the system voltage. This research study about voltage fluctuation on AC railway electrification. The method used in this study is to simulate a model of railway electrification such as traction substations, overhead electrification and rail infrastructure. System modeling is done using open power net software. The results of this simulation show the condition of voltage fluctuations on the bus, overhead wire and pantograph sides